Suture less 3D mesh repair of sliding inguinal hernia: a case report - Bagul, Abhijit; Chougle, Qurratulain; Kumar, Meena; ., Nandkishore; Khan, Naseem; Murali, Sridevi (International Journal of Research in Medical Sciences, 2017)
Sliding hernias involving the urinary bladder are rare, almost exclusively seen in men. As a result of slipping of the posterior parietal peritoneum on the underlying retroperitoneal structures, the posterior wall of the sac is not formed of the peritoneum alone, but by a portion of the bladder on either side. This case report presents the case of a 54 year old male patient with Right groin swelling since two years, gradually increasing in size with complaints of pain at the site of the swelling prior to voiding and also, an increase in the size of the swelling on retaining urine for a long duration. Based on clinical and radiological findings patient was diagnosed with Sliding inguinal hernia with bladder component, and underwent Open suture less 3D Mesh repair, with replacement of the bladder in the retroperitoneal space. The aim of this case report is to highlight the successful surgical management of a rare sliding hernia involving the urinary bladder using suture less 3D mesh repair.